2022
DOI: 10.1126/sciadv.abn8281
|View full text |Cite
|
Sign up to set email alerts
|

Allelic shift in cis-elements of the transcription factor RAP2.12 underlies adaptation associated with humidity in Arabidopsis thaliana

Abstract: Populations of widespread species are usually geographically distributed through contrasting stresses, but underlying genetic mechanisms controlling this adaptation remain largely unknown. Here, we show that in Arabidopsis thaliana , allelic changes in the cis-regulatory elements, WT box and W box, in the promoter of a key transcription factor associated with oxygen sensing, RELATED TO AP 2.12 (RAP2.12), are responsible for differentially regulating tolerance to drought and flooding. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…Thus, there was no necessary connection between evolutionary relationship and presence/absence variation. Recently, it has been found that allelic changes of cis-regulatory elements of RAP2.12 are responsible for differentially regulating tolerance to drought and flooding in Arabidopsis (Lou et al, 2022). Therefore, in addition to presence/absence variation, variation in cis-acting elements should be taken into consideration when characterizing certain CaM/CML genes.…”
Section: Hvcams/cmls In Different Barley Genotypesmentioning
confidence: 99%
“…Thus, there was no necessary connection between evolutionary relationship and presence/absence variation. Recently, it has been found that allelic changes of cis-regulatory elements of RAP2.12 are responsible for differentially regulating tolerance to drought and flooding in Arabidopsis (Lou et al, 2022). Therefore, in addition to presence/absence variation, variation in cis-acting elements should be taken into consideration when characterizing certain CaM/CML genes.…”
Section: Hvcams/cmls In Different Barley Genotypesmentioning
confidence: 99%
“…This result contrasted with previous studies on woody plants and lowland regions (Wang et al., 2022 ), but was similar to Saxifraga (Liu et al., 2021 ). A recent physiological study also found that populations of the herbaceous plant Arabidopsis thaliana in Tibet suffered from higher drought stress compared to lowland populations in Sichuan, China (Lou et al., 2022 ). The narrow‐ranging species of Gentiana , which are mainly distributed in alpine mountain regions, might also suffer from higher drought stress than wide‐ranging species, thus showing a positive correlation with PWQ.…”
Section: Discussionmentioning
confidence: 98%
“…The increase in leaf angle and petiole elongation under submergence has been reported previously for flood-adapted species with aerenchyma-rich tissues, such as species from the genus Rumex and Rorippa ( Cox et al 2003 ; Pierik et al 2005 ; Sasidharan and Voesenek 2015 ) as well as in Arabidopsis , which lacks aerenchyma ( van Veen et al 2016 ). However, unlike most previous submergence research on Arabidopsis ( Vashisht et al 2011 ; Gonzali et al 2015 ; van Veen et al 2016 ; Yuan et al 2017 ; Yeung et al 2018 ; Bui et al 2020 ; Lou et al 2022 ), our submergence treatments were performed in the light and the decline in internal oxygen concentrations might have been more gradual, as light availability during submergence allows for some underwater photosynthesis and supports oxygen production and carbon assimilation, making the stress milder than in the absence of light ( Vashisht et al 2011 ). This may also explain why we do not see a strong evidence of a physiological drought during the post-submergence phase in our experiments, in contrast to what has been reported previously ( Fukao et al 2011 ; Sasidharan and Voesenek 2015 ; Tamang and Fukao 2015 ; Yeung et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%